2022
DOI: 10.1002/adma.202200117
|View full text |Cite
|
Sign up to set email alerts
|

Dative Epitaxy of Commensurate Monocrystalline Covalent van der Waals Moiré Supercrystal

Abstract: Realizing van der Waals (vdW) epitaxy in the 80's represents a breakthrough that circumvents the stringent lattice matching and processing compatibility requirements in conventional covalent heteroepitaxy. However, due to the weak vdW interactions, there is little control over film qualities by the substrate. Typically, discrete domains with a spread of misorientation angles are formed, limiting the applicability of vdW epitaxy. Here we report the epitaxial growth of monocrystalline, covalent Cr5Te8 2D crystal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…While there has been considerable interest in the synthesis of vdW multilayer stacks, relatively few studies have investigated the effect of vdW layers on the growth-related aspects of overlayers. vdW epitaxy, a term coined by Koma and co-workers, where heteroepitaxial growth of a vdW layer proceeds on another vdW-bonded substrate or on a three-dimensional solid substrate (with covalent, ionic, and/or metallic bonding) and vice versa , has been demonstrated in a variety of materials. Koma and co-workers suggested that vdW bonding across, and the lack of dangling bonds on, the substrate surface weaken interactions between the adatoms and substrate, enhancing the mobility of the adspecies and resulting in better crystallinity of the deposited film.…”
Section: Introductionmentioning
confidence: 99%
“…While there has been considerable interest in the synthesis of vdW multilayer stacks, relatively few studies have investigated the effect of vdW layers on the growth-related aspects of overlayers. vdW epitaxy, a term coined by Koma and co-workers, where heteroepitaxial growth of a vdW layer proceeds on another vdW-bonded substrate or on a three-dimensional solid substrate (with covalent, ionic, and/or metallic bonding) and vice versa , has been demonstrated in a variety of materials. Koma and co-workers suggested that vdW bonding across, and the lack of dangling bonds on, the substrate surface weaken interactions between the adatoms and substrate, enhancing the mobility of the adspecies and resulting in better crystallinity of the deposited film.…”
Section: Introductionmentioning
confidence: 99%
“…These can be constructed via twisting angles or lattice mismatching at the interface of layered materials. To date, a vast majority of studied moiré systems have been based on two-dimensional (2D) materials with interlayer van der Waals (vdW) interactions, such as twisted bilayer graphene (TBG), , graphene/BN heterostructures, and transition-metal dichalcogenide (TMDC) heterostructures. In particular, the band structure of TBG can be tuned by rotational twisting, inducing superconductivity or Mott insulating behavior. , Contrary to vdW materials, covalent materials are terminated with unsaturated dangling bonds on the surface, usually resulting in strong interface interaction with epitaxial films on top . Therefore, preparing moiré superstructures in a 2D film on a covalent substrate is challenging; however, it may result in extraordinary properties, especially for a topological film.…”
mentioning
confidence: 99%
“…XPS spectra show that the positions of binding energy peaks of the three samples are almost the same, consistent with that reported by Shimada et al The peaks located at around 575.5 and 585.9 eV are attributed to Cr 2p 2/3 and Cr 2p 1/2 , while those located at around 572.2 and 582.4 eV are attributed to Te 3d 5/2 and Te 3d 3/2 , respectively. However, it is difficult to obtain reliable composition and valence information from XPS spectra as in the two-dimensional Cr 1−δ Te films. , It can just be observed that the Cr content of Cr 3 Te 4 and Cr 5 Te 8 is lower than that of CrTe. For Cr 3 Te 4 , Chua et al assigned the two broad peaks at 572 and 582 eV to three components containing Te 3d 5/2 (Te 3d 3/2 ), Cr 2p 3/2 (Cr 2p 1/2 ), and Te from Te x O y , but it seems to be more appropriate to assign them to different valence states of Cr instead of Te x O y …”
Section: Resultsmentioning
confidence: 99%